Itinerários e "lutas": o engajamento de lideranças dos movimentos homossexual e LGBT em Sergipe (1981-2012) - Melo, Marcos Ribeiro de (2013)
This work investigated the engagement of leaders from the gay and LGBT movements in Sergipe through the itineraries from twenty-five activists between 1981 and 2012. The research focused in the emergence of the mobilization, changes of "struggles" over the decades, the social networks (formal and informal) forged by the leaders and the connection of these agents with the "causes . For this purpose were conducted biographical interviews, documentary analysis and observations of events and meetings. The data indicate that the political opening in the early 1980s was an important political opportunity for the emergence of a homosexual mobilization that period in Sergipe, as well as the networks established with others brazilian homossexual associations, especially with Grupo Gay da Bahia. However, only from the second half of the decade, with the advent of HIV / AIDS and the approximation to the state, it was possible to start a process of institutionalization of the mobilization that was consolidated in the following decades. State investments in "HIV" and the "recognition of social vulnerability" of homosexuals, in the 1990s, had created new sexual identities and defined new "flags" that were beginning to emerge on the LGBT political scene. This other approach with the state in the 2000s, held in Aracaju with the political rise of the PT and PCdoB, enabled some leaders began to be part of the state in advising, committee positions and coordinations. At the same time, nationally, and in line with the movement, the federal government invested in the training of new leaders and strengthening of existing associations, which confirms the political-ideological convergence between the two political spheres.